Clinical utility of antimicrobial susceptibility measurement plate covering formulated concentrations of various ophthalmic antimicrobial drugs - Tou N (Dove Medical Press, 2016)
Norihiko Tou,1 Ryohei Nejima,2 Yoshifumi Ikeda,3 Yuichi Hori,4 Kaoru Araki-Sasaki,5 Kazunori Miyata,2 Yoshitsugu Inoue,3 Akihiko Tawara1 1Department of Ophthalmology, University of Occupational and Environmental Health, Fukuoka, 2Miyata Eye Hospital, Miyazaki, 3Division of Ophthalmology and Visual Science, Faculty of Medicine, Tottori University, Tottori, 4Department of Ophthalmology, Toho University Sakura Medical Center, Chiba, 5Ideta Eye Hospital, Kumamoto, Japan Purpose: The purpose of this study was to evaluate the clinical utility of SG17, an ophthalmic antimicrobial susceptibility measurement plate.Design: This was a multicenter, retrospective, observational study.Patients and methods: Using clinical isolates from patients with ocular infections, drug susceptibility testing using the Clinical Laboratory and Standards Institute standards was routinely conducted at five facilities. The minimum inhibitory concentrations of the isolated strains were determined using SG17 at the Research Foundation for Microbial Diseases of Osaka University. The records of antimicrobial drugs used and the therapeutic course were evaluated for all cases. The susceptibility results from SG17 and routine methods used at each facility were compared.Results: A total of 112 bacterial strains were isolated from 92 patients. Of these cases, keratitis was the most common (52.2%), followed by conjunctivitis (21.7%) and others (26.1%). Principal signs and symptoms resolved in all patients, indicating that therapeutic effects had been achieved. With SG17, drug susceptibility was determined in 98.9% of isolates compared with 30.4% of isolates determined using conventional methods. By adapting the Clinical Laboratory and Standards Institute standards to SG17 results, we found that 91.3% of patients were susceptible and 7.6% were resistant. In five patients, drugs with a resistant evaluation were initially administered with no effect, and the patients were then switched to drugs with a susceptible evaluation with final resolution, indicating agreement of clinical results with SG17.Conclusion: SG17 can be used to determine drug susceptibility to antimicrobial agents currently used in ophthalmic practice. SG17 is useful for selecting antimicrobial drugs. Keywords: ophthalmic antimicrobial agent, drug susceptibility, minimum inhibitory concentration, Clinical Laboratory and Standards Institute